Physical activity: the key to cardiometabolic risk reduction in obstructive sleep apnoea. Issue 4 (11th October 2018) - Mendelson, Monique; Flore, Patrice
Obstructive sleep apnoea (OSA) is a prevalent sleep disorder, with recent estimates reporting prevalence ranging between 3% and 17% for moderate-severe OSA depending on age and sex [1]. Physical activity is a pivotal variable for cardiometabolic risk reduction in obstructive sleep apnoea http://ow.ly/QJeO30lZHvq